The Relationship between Adolescent Characteristics and The Level of Knowledge about Reproductive Health in RW 03 Tanah Tinggi Village of JoharBaru Sub-District - Ni Nyoman Sri Artina Dewi; Agustina Ida Pratiwi (Journal of Midwifery, 2021)
Some of the factors that influence adolescent reproductive health are, among others, knowledge, personality, attitude and environment. This study generally aimed to determine the relationship between adolescent characteristics and adolescent knowledge about reproductive health. This research was an analytical study with a cross-sectional study approach, using primary data obtained from a questionnaire, which was given to adolescents totaling 56 respondents aged 10-19 years. Data processing used the SPSS program 20. Data analysis in this study was univariate and bivariate analysis with Chi-Square statistical tests. The results showed that there was a relationship between age and adolescent knowledge about reproductive health with a p value of 0.009 (p <0.05), there was no relationship between gender and adolescent knowledge with a p value of 0.103 (p> 0.05), and there was a relationship between sources of information and knowledge with a p value of 0.006 (p <0.05). From the results of this study, the researchers suggested that adolescents should continue to improve their knowledge regarding reproductive health, either face-to-face or mass media